Development of Green Accounting for Sustainable Monitoring and Reporting in Modern Business - Arfenita Cahyaningrum; Muhammad Indra Wardana; Hwihanus Hwihanus (Ethics and Law Journal: Business and Notary, 2024)
In an era of climate change and sustainability becoming a major global focus, green accounting has emerged as a critical response to these demands. Green accounting is an accounting approach that includes the ecological impact of economic activity, going beyond the traditional focus on profitability and financial performance. The main goal of green accounting is to measure, monitor and report economic activities that impact the environment in a holistic manner. Implementing green accounting helps companies identify, measure and manage the environmental impact of their activities, improve operational efficiency and meet regulatory obligations. However, the main challenges in implementing green accounting include the availability of accurate data, the complexity of measurement methods, implementation costs, and the difficulty of measuring indirect impacts. Additionally, companies need to ensure compliance with varying reporting standards across jurisdictions and change corporate culture to integrate sustainable practices. However, green accounting can increase transparency, accountability and a company's reputation in the eyes of external stakeholders such as investors, consumers and regulators. By reporting accurate data on environmental impacts, companies can strengthen stakeholder trust, meet their expectations and drive innovation. Thus, green accounting is not only a tool for measuring environmental impact but also an important strategic step to achieve long-term sustainability in modern business. This research explores the development of green accounting in the context of modern business and identifies best practices to overcome the challenges faced.